Education in a marriage market model without commitment - Raphaela Hyee (Queen Mary University of London, School of Economics and Finance, 2011)
This paper develops a model that combines intra-household bargaining with competition on the marriage market to analyse women's and men's incentives to invest in education. Once married, spouses bargain over their share of total household income. They have the option of unilateral divorce and subsequent remarriage. Through this channel, the marriage market situation (the quality of prospective spouses and the distribution of resources in other couples) influences the distribution within existing couples. Individuals differ in their educational attainment, and more educated individuals contribute more to household income. I use this model to study the impact of changes in the rates of educational attainment of men and women on intra-household distribution. An increase in the number of women who obtain a university degree over an above the number of men who do so benefits men without degrees; university educated men, however, are not able to translate this change on the marriage market into a significantly larger share of household income. Hence, men's incentive to invest in education decreases if more women become educated. Even without assuming any heterogeneity in tastes between men and women, equilibria arise in which men and women decide to become educated at different rates.
Keywords: D13; D31; I24; 330; family bargaining; gender education gap; investment in education